Access to Internet of People With Disabilities - Fatoş Subaşıoğlu (Türk Kütüphaneciliği)
The last decade has producted a revolution in the world of Internet and computer technology for many disabled people. Especially, with the help of adaptive technology, for example, deaf-blind people can communicate over telephone networks and severely visaully impaired people can read a computer screen directly with the help of speech synthesis or automatically generated Braille displays. People with physical disabilities can use personel computers by blowing. It’s even possible to control computers by using the voice. However, currently, the largest problem is that WWW pages are increasingly developed with pictures, images, audio and video clips carrying much of the information. For this reason, the aims of this article are twofold: first, to give some information about products of adaptive technologies for people with disabilities, and second, to give some design examples about Web pages for this people.